The impact of a yoga training program on muscle contractile properties in elite soccer players - Pereira, A.; Madeira, R.; Monteiro, L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Yoga challenges the body in many ways, and being a very different methodology to normal training, it can be an important complementary technique for more extensive training or even replace traditional methods, with a highly positive impact on football practice and training [1]. Considering the results showing the potential of Yoga to reduce perceived propensity to reduce injuries and general fatigue, its integration into football training can be considered [2]. Our hypothesis is that Football players undergoing additional Yoga training, improve the lower limbs muscles contractile properties[3,4].